#Blacklivesmatter: Leveraging family collaboration in pain management. Issue 2 (March 2016) - Booker, Staja Q.
Abstract : Abstract: Managing pain is a constant challenge for many critical care nurses. It may be even more difficult to manage pain in ethnically diverse patients, such as Black Americans. However, family collaboration can assist nurses to effectively assess and treat pain while also respecting and incorporating personal and cultural preferences. Abstract : Pain may be more difficult to manage in ethnically diverse patients, such as Black Americans. Learn how family collaboration can assist nurses to effectively assess and treat pain while also respecting and incorporating personal and cultural preferences.